User-Perceived Negative Respiratory Symptoms Associated with Electronic Cigarette Use. (15th December 2020) - Soule, Eric K; Bode, Kendall M; Desrosiers, Abigail C; Guy, Mignonne; Breland, Alison; Fagan, Pebbles
Abstract: Introduction: Electronic cigarettes (ECIGs) expose users to an aerosol containing chemicals, which could affect the respiratory system negatively. This study examined negative respiratory symptoms associated with ECIG use. Methods: In 2019, adult current ECIG users from 24 US states who reported experiencing negative respiratory symptoms from ECIG use ( n = 49; 44.9% women; mean age = 35.2, SD = 11.5) completed an online survey and brainstormed statements that completed the prompt: "A specific negative effect or symptom related to my breathing, nose, mouth, throat, or lungs that I have experienced from vaping/using my e-cigarette is..." Participants sorted the final list of 56 statements into groups of similar content and rated statements on how true they were for them. Multidimensional scaling analysis identified thematic clusters. Results: Eight ECIG use respiratory symptom clusters identified in analysis included Mucus and Congestion, Fatigue, Throat Symptoms, Breathing Problems, Mouth Symptoms, Chest Symptoms, Illness Symptoms, and Nose and Sinus Symptoms. Highly rated (ie, most common) symptoms included dry throat or mouth, fatigue during physical activity, coughing, shortness of breath, excessive phlegm, and bad taste in mouth. Mean cluster ratings did not differ based on lifetime cigarette smoking status (100 lifetime cigarettes smoked), but current cigarette smokers (ie, dual users) rated the Fatigue, Breathing Problems, Mucus and Congestion, and Nose and Sinus Symptoms clusters higher than noncurrent cigarette smokers. Conclusions: Participant-identified respiratory symptoms perceived to be ECIG related, many similar to cigarette smoking symptoms. Future research should assess if these symptoms are associated with other negative health outcomes. Implications: ECIG use exposes users to chemicals that may have negative health impacts on the respiratory system. Limited research has examined the broad range of negative respiratory symptoms associated with e-cigarette use. This study identified that ECIG–cigarette users perceive their ECIG use to be associated with negative respiratory symptoms. Many e-cigarette user-reported negative respiratory symptoms are similar to those associated with cigarette smoking, though some appear unique to e-cigarette use. Future research should continue to monitor respiratory symptoms reported by ECIG users and whether these are associated with health outcomes over time.